Standardized Learning Assessment in Languages Core Curricula: A Study at the Autonomous University of Baja California, México - Gutiérrez-Benítez, Jorge Gustavo (2023)
Objective. The study presents the structure and components of a standardized departmental test applied to one of the subjects of outmost curricular relevance for the core curricula of the Faculty of Languages (FL). It also presents psychometric evaluation results of the evaluation performed on the test. Method. To conduct this standardized test, the study used the methodology developed by the Educational Research & Development Institute (Contreras Niño, 2000; Contreras Niño & Backhoff Escudero, 2004). The test is based on the proposed psychometric model by Nitko (1994), designed to construct large-scale criterion-referenced tests. The study sample consisted of 260 first-semester students from FL in the state. The psychometric analysis followed the Item Response Theory to measure features such as the discrimination index, discrimination coefficient, and difficulty index. Results. Average values obtained from the psychometric analysis of the test exceeded discrimination index and coefficient standards (.32), especially those obtained in the thematic unit of greatest curricular relevance for the studied subject. Also, a general average difficulty and an acceptable distribution of said difficulty in the items were observed. Conclusions. The obtained values for the reliability and validity features evidenced the instrument´s quality. This directly contributes to the certainty of the level of mastery that the students show in relation to the knowledge universe represented in the test; this situation has a high impact because of the relevance of this subject.